Upaya Pengurangan Sampah Plastik melalui Integrasi Ecobrick oleh Kelompok 98 di Kelurahan Bakung, Kecamatan Teluk Betung Barat, Kota Bandar Lampung - Herlina Kurniati; Riski Romadoni; Rosalia Keisa Puti Lutfa; Elsa Meiani; Deah Monica; Muhamad Tegar Sabili (Lembaga Pengembangan Kinerja Dosen, 2025)
Plastic waste remains a pressing issue in Bakung Village, Teluk Betung Barat Subdistrict, Bandar Lampung City, as it affects public health, reduces environmental aesthetics, and triggers flooding due to poor waste management systems. In response, the 2025 Integrated Community Service Program (KKN) of UIN Raden Intan Lampung, through Group 98, applied the ecobrick method as a community-based alternative for managing plastic waste. This study adopted an appropriate technology approach with descriptive qualitative methods, namely observation, interviews, and documentation, to analyze field conditions and evaluate program outcomes. The results demonstrated the successful construction of a ±1-meter monument spelling “Bakung,” which incorporated more than 350 used plastic bottles as ecobricks. Beyond beautifying the environment and serving as a landmark, the monument inspired local residents to participate actively in sorting waste and making ecobricks. Community involvement was particularly visible during material collection and production stages, reflecting the effectiveness of a participatory approach. Additionally, this activity had an educational impact by showing that plastic waste can be transformed into useful and aesthetically valuable products. Although limited time and energy became major challenges, these were addressed through continuous mentoring. Overall, the program proved that ecobricks offer a practical and innovative solution for reducing plastic waste and contribute to achieving Sustainable Development Goals (SDGs) 11 and 12.